Pemberian Hak Paten Vaksin Covid-19 Menurut Agreement on Trade-Related Aspects of Intellectual Property Rights (TRIPs) - Calvin Giovanni, Ericko; Atmadja, Hendra Tanu (Civil Officium: Journal of Empirical Studies on Social Science, 2022)
Intellectual Property Rights, abbreviated as KI (Intellectual Property), has developed from time to time. This development was increasingly seen with the establishment of Trade Related Aspects of Intellectual Property Rights (TRIPs) in 1994 in the Uruguay Round. In TRIPs various IP issues are regulated, one of which is Patents. As a form of intellectual property rights, the granting of a patent by the state to a work or invention in the field of technology is an award to the inventor. These ideas can be realized in the form of processes or objects that are known and used in everyday life. All patent registrations must refer to the TRIPs that have been agreed upon by the participating countries. In 2019, a deadly virus was detected from the city of Wuhan, China, which was initially categorized as a form of pneumonia that attacks local residents. The World Health Organization (WHO) identified the virus as a new type of Corona Virus in January 2020, and gave it an official name as Corona Viruses Disease 2019 (Covid-19). Various countries have made efforts to overcome the malignancy of Covid-19, one of the efforts made is to try to find a drug or vaccine as a solution to the pandemic which is a world problem. Here, the author discusses whether the Covid-19 vaccine can be granted a patent under TRIPs and whether the patent granted is valid for the entire region or is territorial. The research method used is normative by reviewing the literature or secondary data. The conclusion from the above discussion shows that the Covid-19 vaccine can be granted a patent with a territorial application based on TRIPs.